2008
DOI: 10.1371/journal.pgen.1000097
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Morphogenesis, Dendrite Development, and Synapse Formation in Cerebellum Require both Bcl-w and the Glutamate Receptor δ2

Abstract: Bcl-w belongs to the prosurvival group of the Bcl-2 family, while the glutamate receptor δ2 (Grid2) is an excitatory receptor that is specifically expressed in Purkinje cells, and required for Purkinje cell synapse formation. A recently published result as well as our own findings have shown that Bcl-w can physically interact with an autophagy protein, Beclin1, which in turn has been shown previously to form a protein complex with the intracellular domain of Grid2 and an adaptor protein, nPIST. This suggests t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 54 publications
3
57
0
Order By: Relevance
“…69 BCL-2, another pro-survival BCL-2 family protein, is also required for the regulation of mitochondrial length in Purkinje cell processes. 59 Yet, unlike the case of Bcl-xL, quantitative electron microscopy revealed a significant increase in mitochondrial length in BCL-2 </< dendrites, as compared to wild type dendrites in the mouse. Mitochondria in BCL-2 </< mice often contained points where they became constricted, suggests that the elongation of mitochondria might be due to the inhibition or slowdown of the mitochondrial fission process.…”
Section: Emerging Evidence For the Role Of Bcl-2 Family Proteins In Tmentioning
confidence: 89%
See 1 more Smart Citation
“…69 BCL-2, another pro-survival BCL-2 family protein, is also required for the regulation of mitochondrial length in Purkinje cell processes. 59 Yet, unlike the case of Bcl-xL, quantitative electron microscopy revealed a significant increase in mitochondrial length in BCL-2 </< dendrites, as compared to wild type dendrites in the mouse. Mitochondria in BCL-2 </< mice often contained points where they became constricted, suggests that the elongation of mitochondria might be due to the inhibition or slowdown of the mitochondrial fission process.…”
Section: Emerging Evidence For the Role Of Bcl-2 Family Proteins In Tmentioning
confidence: 89%
“…The published evidence suggests that mitochondrial morphogenesis proteins, perhaps through direct modulation of BCL-2 family proteins, participate in this process. Since mitochondrial morphogenesis proteins, including Mfn2, Fis1 and Drp1, can interact with BCL-2 family proteins, 24,58,59 one could predict that direct molecular interactions between these proteins (e.g., Drp1, Mfn2) and BCL-2 family members take part in the regulation of the mitochondrial steps in apoptosis. Immunoprecipitation studies demonstrated that in healthy cells Mfn1 and Mfn2 interact with Bak, 54 yet upon induction of apoptosis the interaction of Bak with Mfn2 was no longer detectable.…”
Section: Mitochondrial Morphogenesis and The Omm Permeabilizationmentioning
confidence: 99%
“…Anti-apoptotic Bcl-2 family members have been shown to perturb mitochondria in the absence of any cell death phenotype hinting that these proteins may have a role in mitochondrial remodelling within healthy cells that is separate to their role in protecting against apoptosis (Autret and Martin, 2009;Berman et al, 2008;Delivani et al, 2006;Liu et al, 2008;Sheridan et al, 2008). Thus, increased…”
Section: Discussionmentioning
confidence: 99%
“…While Bcl-w deficiency in the brain produces no cell death defects, mitochondria in purkinje cells are elongated and these cells have abnormal synapses and dendrites, possibly due to impaired mitochondrial fission (Liu et al, 2008). Bcl-xL has also been implicated in regulating mitochondrial morphology in neurons.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…A direct correlation between increased number of mitochondria and increased number of spines and synapses has been demonstrated in primary neuronal culture (Liu and Shio, 2008), implicating that mitochondrial proliferation is a biological process facing energy demand during neuronal growth. In the fetus, the respiratory chain complexes are assembled and functional at early stages of development in the brain as in many other organs, and oxidative phosphorylation deficiency may have deleterious consequences (Minai et al, 2008).…”
Section: Introductionmentioning
confidence: 94%